2015
DOI: 10.1002/mc.22350
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the precursor microRNAs and aflatoxin B1‐related hepatocellular carcinoma

Abstract: The altered expression of some microRNAs (miRNAs) is observed in hepatocellular carcinoma (HCC); however, the genetic polymorphisms in the precursor miRNAs (pre-miRNAs) in aflatoxin B1 (AFB1)-related HCC have not yet been investigated. A hospital-based case-control study, including 1,706 HCC cases and 2,270 controls without any liver diseases or tumors, was conducted in a high AFB1 exposure area of China to assess the relationship between 48 polymorphisms in the pre-miRNAs and AFB1-related HCC risk and prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The level of miR-1268a expression in cancerous tissues was analyzed using our previously published TaqMan quantitative reverse transcription-PCR technique24. In this study, the relative amount of miR-1268 to internal control U6 was calculated as 2 −ΔCt method, where ΔCt = (Ct miR-1268a  − Ct U6 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of miR-1268a expression in cancerous tissues was analyzed using our previously published TaqMan quantitative reverse transcription-PCR technique24. In this study, the relative amount of miR-1268 to internal control U6 was calculated as 2 −ΔCt method, where ΔCt = (Ct miR-1268a  − Ct U6 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among these microRNAs, microRNA-1268a (miR-1268a), which is an important abundant microRNA encoded by MIR1268A gene and functionally involves in embryogenesis and cell differentiation23, is particular concern in our research projects. Our previous data from a large molecular epidemiological investigation have exhibited that the genetic variables in the seeding region of miR-1268a were correlated with tumor angiogenesis and may involve in the carcinogenesis of HCC24. This suggests a possible relationship between miR-1268a and the prognosis of HCC characterized by rich blood vessels.…”
mentioning
confidence: 92%
“…The same research group found that miR-24, which has been reported to be an “oncomir” [103], was upregulated in liver tumors from patients who resided in regions with high AFB1 exposure [104]. Further, in a large case-control hospital study in China that investigated polymorphisms in pre-miRNAs as potential risk and prognostic biomarkers of AFB1-related HCC, rs28599926 in miR-1268a was identified as one such candidate [105]. …”
Section: Epigenetic Effects Associated With Carcinogenic Chemicalsmentioning
confidence: 99%
“…This could be caused by the aflatoxin ability to determine the mutation of the p53 tumor suppressor gene, which in normal conditions induces the apoptosis processes [74][75][76][77] . The risk of HCC increases when the exposure occurs in the presence of HBV infection, as occurs in the Chinese population [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] .…”
Section: Aflatoxinsmentioning
confidence: 99%